Effect of Ex Situ Modification of Bacterial Cellulose with Organosilane Coupling Agent on Drug Delivery Properties - Nascimento, Ariane Maria da Silva Santos; Silva, Jhonatan Miguel; de Lima, Idglan Sá; Furtini, Josy Anteveli Osajima; Ribeiro, Sidney José Lima [UNESP]; Muniz, Edvani Curti; da Silva Barud, Hernane; Silva-Filho, Edson Cavalcanti (Springer Nature, 2024)
Bacterial cellulose (BC) is a polymer structurally like plant cellulose, but with superior physicochemical properties. BC and the several functionalization possibilities exhibited by cellulosic polymers have led to new versatile multifunctional materials. Several studies have investigated modifications to the BC surface to make it effective, for example, in antibacterial and adsorption terms, so, BC was functionalized with the silanes 3-Aminopropyltriethoxysilane and 3-glycidyloxypropyltrimethoxysilane in three different proportions. Although the diffractograms of the modified samples did not exhibit significant changes, this indicates FTIR spectra, with primary amino groups and stretching the vibration of Si–O–Si. Regarding drug adsorption kinetics, the samples exhibited a better fit with the pseudo-second-order model the increase in pH value promoted an increase in the maximum amount of adsorption, with values of q = 98.92 mg g−1 for Ibuprofen and q = 98.50 mg g−1 for Ketoprofen. In the in vitro release tests using gastric fluid, the release rate achieved higher values compared to PBS environments. The highest release values were observed with the samples modified by method 2 and particularly, the BC70-A sample showed the highest percentage of drug release. Controlled release can provide a smoother and prolonged release profile, resulting in a more stable response to the medication. Silanized BC showed greater inhibition for Staphylococcus aureus. Graphical Abstract: (Figure presented.)
Keywords: Adsorption; Bacterial cellulose; Drugs; Functionalization